Unusual Talaromyces marneffei and Pneumocystis jirovecii coinfection in a child with a STAT1 mutation: A case report and literature review - Yang, Qin; Yu, Chendi; Wu, Yue; Cao, Ke; Li, Xiaonan; Cao, Weiguo; Cao, Lichao; Zhang, Shenrui; Ba, Ying; Zheng, Yuejie; Zhang, Hezi; Wang, Wenjian (Frontiers in Immunology, 2023)
Talaromyces marneffei and Pneumocystis jirovecii are the common opportunistic pathogens in immunodeficient patients. There have been no reports of T. marneffei and P. jirovecii coinfection in immunodeficient children. Signal transducer and activator of transcription 1 (STAT1) is a key transcription factor in immune responses. STAT1 mutations are predominately associated with chronic mucocutaneous candidiasis and invasive mycosis. We report a 1-year-2-month-old boy diagnosed with severe laryngitis and pneumonia caused by T. marneffei and P. jirovecii coinfection, which was confirmed by smear, culture, polymerase chain reaction and metagenome next-generation sequencing of bronchoalveolar lavage fluid. He has a known STAT1 mutation at amino acid 274 in the coiled-coil domain of STAT1 according to whole exome sequencing. Based on the pathogen results, itraconazole and trimethoprim-sulfamethoxazole were administered. This patient’s condition improved, and he was discharged after two weeks of targeted therapy. In the one-year follow-up, the boy remained symptom-free without recurrence.